Profiling and understanding student information behaviour: methodologies and meaning Jennifer Rowley - Jennifer Rowley (Association for Learning Technology, 2003)
This paper draws on work conducted under the Joint Information Systems Committee (JISC) User Behaviour Monitoring and Evaluation Framework to identify a range of issues associated with research design that can form a platform for enquiry about knowledge creation in the arena of user behaviour. The Framework has developed a multidimensional set of tools for profiling, monitoring and evaluating user behaviour. The Framework has two main approaches: one, a broad-based survey which generates both a qualitative and a quantitative profile of user behaviour, and the other a longitudinal qualitative study of user behaviour that (in addition to providing in-depth insights) is the basis for the development of the EIS (Electronic Information Services) Diagnostic Toolkit. The strengths and weaknesses of the Framework approach are evaluated. In the context of profiling user behaviour, key methodological concerns relate to: representativeness, sampling and access, the selection of appropriate measures and the interpretation of those measures. Qualitative approaches are used to generate detailed insights. These include detailed narratives, case study analysis and gap analysis. The messages from this qualitative analysis do not lend themselves to simple summarization. One approach that has been employed to capture and interpret these messages is the development of the EIS Diagnostic Toolkit. This toolkit can be used to assess and monitor an institution's progress with embedding EIS into learning processes. Finally, consideration must be given to integration of insights generated through different strands within the Framework.